Konstruksi Sosial Atlet Perempuan dalam Mengikuti Olahraga Bela Diri Pencak Silat PSHT Rayon Martubung di Kelurahan Besar - Erika BR. Pinem; Rosramadhana Rosramadhana (Departement of Mathematics Education, 2023)
This study aims to obtain data related to the social construction that has been formed in society and residents in the Setia Hati Terate (PSHT) Brotherhood martial arts organization for female athletes who have long joined the PSHT Rayon Martubung martial arts. The method used in this research is qualitative with a descriptive approach. The research was conducted in Martubung, Kelurahan Besar. Data collection techniques were carried out through observation, interviews and documentation from research informants. The results of this study are based on the findings obtained about the background of female athletes participating in pencak silat martial arts, there are several factors such as external and internal influences, the desire to learn pencak silat as self-protection, and the desire to realize ideals by relying on the achievements obtained. The social construction that occurs in female athletes at PSHT Rayon Martubung through three dialectical processes of externalization, objectivation and internalization. Based on the stages of externalization to internalization, it describes that female athletes participate in pencak silat with their own will and no coercion. In addition, the social construction that was built internally, namely in the PSHT Rayon Martubung organization, saw women who were engaged in pencak silat as a good choice and a natural thing. While the social construction that occurs in the external sphere, namely in society appreciates women who participate in pencak silat.